Cyanobacterial Community Structure and Isolates From Representative Hot Springs of Yunnan Province, China Using an Integrative Approach - Keshari, Nitin; Zhao, Yang; Das, Sudipta Kumar; Zhu, Tao; Lu, Xuefeng (Frontiers in Microbiology, 2022)
Cyanobacteria from the representative hot springs of Yunnan Province, China are explored for their diversity and community composition following an integrative approach of cultivation-independent and -dependent studies and further isolation of potential taxa for future biotechnological perspective. 16S rRNA amplicon sequencing of microbial mats in these hot springs with temperature ranging from 38 to 90°C revealed Cyanobacteria and Proteobacteria constituting a bounteous portion of the bacterial community. The combined approach of 16S rRNA amplicon sequencing and phenotypic analysis revealed the diversity of cyanobacteria (a total of 45 genera). Out of these, a total of 19 cyanobacterial taxa belonging to 6 genera and 10 species were isolated as individuals with the possibility of biotechnological utilization. These isolates were subjected to a thorough morphological study and molecular characterization using 16S rRNA gene sequencing for identification and understanding their phylogeny. The identity and phenotypic and genotypic characteristics of 7 cyanobacterial isolates are not identical to any known cyanobacterial species, generating scope for future taxonomic novelties. Preliminary experiments based on high-temperature (50°C) cultivation showed that most of the isolates were thermotolerant and suggested for their high biotechnological usage potential.